ANALISIS PENERAPAN PRINSIP GOOD CORPORATE GOVERNANCE DALAM EVALUASI PERKULIAHAN DOSEN TADRIS IPA - Budiyono Saputro (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2018)
Abstract This article is aimed at analyzing the implementation of Good Corporate Governance in lecture evaluation at Science Department of the Teacher Training and Education Faculty of IAIN Salatiga. The qualitative research was used whereby the primary data were taken from the results of research subject’s questionnaires, while the secondary information were derived from data that had been processed by other researchers. The subjects of this research were the lecturers of the Science Departmen of IAIN Salatiga. The data analysis technique used was the descriptive qualitative. The implications of analysis for applying the principles of Good Corporate Governance at Science Department of IAIN Salatiga in the evaluation of lectures are as follows: the aspect of transparency principle, which means that the head of the Science Department conveys information on lecturer evaluation results in coordination meetings; the aspect of accountability principle, which means that accountability of lecturer evaluation results on their lectures have been established periodically; the aspect of responsibility principle, which means that the department team reports the implementation of lectures evaluation regularly to the Dean and Quality Control Unit; the aspect of fairness principle, that all lecturers are entitled a justice in the assessment in carrying out lectures in the classroom; and the aspect of independence principle, which means that the evaluation of lectures is done without any influences from any party. Keywords: Good Corporate Governance, Lecture Evaluation, and Science Department Abstrak Tujuan penelitian ini adalah menganalisis penerapan Good Corporate Governance dalam evaluasi perkuliahan dosen Tadris Ilmu Pengetahuan Alam (IPA) Fakultas Tarbiyah dan Ilmu Keguruan (ftik) Institut Agama Islam Negeri (IAIN) Salatiga. Jenis penilitian yang digunakan adalah penelitian kualitatif. Sumber data data primer dari hasil kuesioner subjek penelitian dan sekunder informasi dari data yang telah diolah pihak lain. Subyek penelitian ini dosen Tadris IPA FTIK IAIN Salatiga. Teknik analisis data secara deskriptif kualitatif. Adapun Analisis penerapan prinsip-prinsip Good Corporate Governance pada Program Studi Tadris IPA FTIK IAIN Salatiga implikasinya dalam evaluasi perkuliahan adalah sebagai berikut: Aspek prinsip transparansi, Ketua Program Studi Tadris IPA menyampaikan informasi hasil evaluasi dosen dalam rapat koordinasi. Aspek prinsip akuntabilitas bahwa pertanggungjawaban hasil evaluasi dosen dalam perkuliahan telah ditetapkan secara periodik. Aspek prinsip responsibilitas bahwa tim program studi melaporkan pelaksanaan evaluasi perkuliahan kepada dekanat dan Lembaga Penjaminan Mutu secara rutin. Aspek prinsip fairness, bahwa semua dosen berhak sebuah keadilan dalam penilaian dalam melaksanakan perkuliahan di kelas. Aspek prinsip independensi bahwa dalam evaluasi perkuliahan tanpa adanya pengaruh dari pihak manapun. Kata kunci: Good Corporate Governance, Evaluasi Perkuliahan Dosen, dan IPA